Phraseological Units’ Impact on the English Language - Amir Abushaev (Zeta Repository, 2023)
This article’s main focus is the analysis of English phraseological units, one of the most expressive stylistic forms of language expression. This article examines a variety of values related to the nature and organization of the phonological units that make up language phonological books.